(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
This study was conducted to determine the impact of labor disputes, workload, and organizational culture on PT employee job satisfaction. Tirta Investama Bali in Denpasar. The population and sample used in this study were her 65 respondents, all of whom were employees of his PT. Tirta Investama Bali in Denpasar. Data analysis techniques used in this study were multiple linear, we can say: (1) Labor disputes have a significant negative impact on job satisfaction. (2) Workload has a significant negative impact on employee job satisfaction. (3) Organizational culture has a positive and significant impact on employee job satisfaction. (4) Labor disputes, workload and organizational culture have a positive and significant impact on employee job satisfaction. The magnitude of the independent variable’s effect on employee job satisfaction is 99.2%. Looking at the research, PT. In the future, Tirta Investama Bali should be able to distribute tasks fairly and equitably, and all tasks assigned to employees should be adapted to their status and skills..